2009
DOI: 10.1093/geront/gnp008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of TimeSlips, a Creative Expression Intervention Program, on Nursing Home Residents With Dementia and their Caregivers

Abstract: Implementing the TS program in nursing facilities improves the care environment for PWDs. However, additional studies are needed to offer further insights into the mechanisms by which TS improves both staff and resident outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
149
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(155 citation statements)
references
References 10 publications
5
149
0
1
Order By: Relevance
“…One other study found significant improvement on job satisfaction after the introduction of Snoezelen in 24-hour dementia care (van Weert et al, 2005), whereas a study about a creative expression intervention did not yield any significant changes in staff outcomes (Fritsch et al, 2009). However, a comparison between these studies and GRIP is difficult, for GRIP focuses on improving a process rather than providing a new treatment.…”
Section: Discussionmentioning
confidence: 99%
“…One other study found significant improvement on job satisfaction after the introduction of Snoezelen in 24-hour dementia care (van Weert et al, 2005), whereas a study about a creative expression intervention did not yield any significant changes in staff outcomes (Fritsch et al, 2009). However, a comparison between these studies and GRIP is difficult, for GRIP focuses on improving a process rather than providing a new treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results were very similar: participants demonstrated significant cognitive and affective improvement when compared with two comparison groups (one a singing group and one a nontreatment group). Similarly, whilst Anne Basting herself has provided an account of the history and processes of her well-known 'TimeSlips' programme (Basting, 2013), it has also been formally evaluated (Fritsch et al, 2009). The results showed that residents with dementia in the intervention sites were more engaged and alert, and there were more interactions between residents and staff; meanwhile, staff in intervention sites had more positive views of residents and devalued them less than in the control sites.…”
Section: Reminiscence (N=5)mentioning
confidence: 99%
“…Only one study compared drama participation with another art form (Noice, Noice & Staines, 2004), and three used control groups comparing drama participants with non-participants (Fritsch et al, 2009;Noice, Noice & Staines, 2004;Osgood, 1984). Nor, as we noted earlier, has research been conducted on the long-term effects of drama and theatre participation.…”
Section: Conclusion: Areas For Further Researchmentioning
confidence: 99%
“…Timeslips is a group storytelling program that encourages creating expression among patients with AD [20]. Pressure to remember memories from the past can be frustrating for a person with dementia but the Timeslips program alleviates that pressure by relying on creativity and encouragement for imagination [19].…”
Section: Timeslipsmentioning
confidence: 99%